Language variation in classical and modern standard Arabic: The case of interrogation - Moustafa, Enas (AUC Knowledge Fountain, 2017)
This study aims at investigating the functions of interrogatives in classical Arabic and the differences/similarities regarding the syntactic features of interrogatives in classical Arabic and modern standard Arabic. The study depends on gathering data from Classical Arabic (Quran) and Modern Standard Arabic (newspapers). The investigation of this study adopts a qualitative method procedure. The current research focuses on four interrogatives: /kayf/, /matÄ/, /hal/, and /Ê”ayn/. The study identified the functions of interrogatives in classical Arabic: denial, wonder, determination, threat, wish, etc. Furthermore, the study concludes that there are syntactic structures used in both classical Arabic and modern standard Arabic and other structures that are limited to Classical Arabic only or Modern Standard Arabic only. Results of the linguistic analysis of the data suggest that AFL textbooks need to include rhetorical meaning of interrogatives besides the lexical meaning in order to assist foreign learners when dealing with classical texts. It is recommended that the study be replicated on other interrogatives. This may help reveal more functions and syntactic structures associated with specific interrogatives.